Pembelajaran Dasar Microsoft Office Untuk Pengabdian Masyarakat Di SMP Muhammadiyah 1 Kalasan Yogyakarta - Mukrim, Abdul; Sucinta, Hanny Handayani; Mujahidah, Latifatul; Sumarsono, S (Jurnal TUNAS, 2024)
This Community Service Program aims to enhance basic Microsoft Word skills among students of SMP Muhammadiyah 1 Kalasan, Yogyakarta. The program involved 24 students from grades VII and VIII through several stages, including needs assessment, preparation, training, and evaluation. The training focused on introducing basic features, hands-on practice, and creating simple documents such as reports and tables. The methods employed included participatory approaches and practice-based learning to effectively improve students' understanding and skills. Evaluation was conducted through direct observation and assessment of the documents produced by the students. The program results showed significant improvement in students' understanding and ability to use Microsoft Word, particularly in supporting their academic activities. Additionally, the program succeeded in encouraging students to be more confident in utilizing technology for learning. Thus, this program is expected to serve as an initial foundation for strengthening students' technology literacy while providing long-term benefits in supporting educational needs in the digital era. The impact of this activity is also expected to inspire the implementation of similar programs in the future to enhance technological competencies at other educational levels.